STRATEGI BRANDING PARIWISATA BENGKULU OLEH DINAS PARIWISATA PROVINSI BENGKULU - ANANDA AYU PUTRI (Professional: Jurnal Komunikasi dan Administrasi Publik, 2021)
The purpose of this study was to identify and describe the Bengkulu tourism branding strategy carried out by the Bengkulu Province Tourism Office. This research approach is a descriptive qualitative approach. This research uses positioning, differentiation and brand theory. In this study, the researcher used principal informants and key informants based on the purposive sampling technique. Data collection techniques were carried out by means of observation, in-depth interviews, documentation and literature study. The data analysis technique was carried out by means of data reduction, data presentation and drawing conclusions. This study uses a test of the validity of the data by means of triangulation techniques. The results of this study indicate that the branding strategy carried out by the Bengkulu Provincial Tourism Office is by positioning Bengkulu tourism to foreign tourists in order to attract interest to visit Bengkulu and also the need for promotional activities. The Bengkulu Provincial Tourism Office has carried out promotional activities through various media, both print media, electronic media and social media. Until now, the Bengkulu Provincial Tourism Office does not know what things will be highlighted as selling points and the value that differentiates Bengkulu tourism from other provincial tourism. So that Bengkulu Province does not yet have a jointly defined brand. Bengkulu Province still uses the old brand, "The land of Rafflesia".